Biodegradable potential of LLDPE/TiO2-ZnO film in soil and hydrolytic systems targeted for healthcare-related product - Nor Hazliana Harun; Rabiatul Basria S. M. N. Mydin; Srimala Sreekantan; Nurul Sahira Ngaini; Khairul Arifah Saharuddin; Norfatehah Basiron (Journal of Taibah University for Science)
Medical-grade polymers present challenges in long-term healthcare waste management due to resistance in degradation mechanisms. Collaborative nanocomposite technology in biomedical polymers holds promise for enhancing biodegradability. This study examined the biodegradability of LLDPE/TiO2-ZnO film in various environmental conditions (compost soil, pond soil, coastline, and landfill soil, hydrolytic and simulated body fluid models) and further assessment using field emission scanning electron microscopy (FESEM) and Coupled Plasma Optical Emission spectroscopy. Nanocomposite present in LLDPE polymer could enhance the biodegradability potential of the film possibility via hydrolysis and free radicals’ activities, especially in high moisture content environment. Deformation holes in the film were observed via FESEM confirming degradability activities. The biodegradability rate is also could be influenced by microbe-rich environments. The insights gained from this study have the potential to contribute to the advancement of biodegradable polymers and the improvement of waste management technology in the healthcare industry.